New diagnostic modalities and emerging treatments for neonatal bone disease. (November 2018) - Borg, Stephanie A.; Bishop, Nicholas J.
Abstract: Bone disease in the neonatal period has often been regarded as an issue affecting premature infants, or a collection of rare and ultra-rare disorders that most neonatologists will see only once or twice each year, or possibly each decade. The emergence of targeted therapies for some of these rare disorders means that neonatologists may be faced with diagnostic dilemmas that need a rapid solution in order to access management options that did not previously exist. The diagnostic modalities available to the neonatologist have not changed a great deal in recent years; blood tests and radiographs still form the mainstays with other techniques usually reserved for research studies, but rapid access to genomic testing is emergent. This paper provides an update around diagnosis and management of bone problems likely to present to the neonatologist.